The Victorian Government’s prison privatisation project (1992-2010): The pathway to cost efficiency? A longitudinal analysis - Sands, Valarie J.; Hodge, Graeme A. (The journal of contemporary issues in business and government, 2014)
This article evaluates the operational efficiency of the Victorian prison system since the introduction of the neoliberal prison privatisation policy in 1992 through to the period of the next Government (from 1999), ending in 2010. The analysis explores the origin of the Victorian prison system’s reform, before focussing on an evaluation of the prison privatisation policy and the prison system’s consequent transition from a public to a mixed public-private system. This partially-privatised system comprised various combinations of public and private management and infrastructure. One of the Government’s dominant pro-privatisation promises was that introducing private sector competition to the prison system would ensure a more cost-efficient prison system. This study investigates the policy claim that competition and privatisation would yield cost savings for the prison system. The findings indicate that whilst significant cost savings were achieved in the period shortly after privatisation reforms occurred, longer term costs rose significantly as well. Overall, then, Government policy promises about efficiency gains associated with prison privatisations were not realised in the long-term